Preparation of ceramic pigment from tanned leather waste - Junlar, Pranee; Nawaukkaratharnant, Nithiwach; Srekumwong, Orawan (Bulletin of Applied Sciences, 2022)
This research studies on the utilization of tanned leather waste from tannery industries composed of chromium for producing the ceramic pigment.Firstly, the chemical composition and phase composition of the waste were characterized using X-ray fluorescence (XRF)and X-raydiffraction (XRD), respectively. The waste fired at 1100 °C, which the main phase was chromium (II) oxide (Cr2O3), was used as chromium source to create the ceramic pigment. The fired waste was wet-mixed with ZnO and Al(OH)3 to create the pink pigment (Zn-Al-Cr system) and with ZnO and Fe2O3 to create the brown pigment (Zn-Fe-Cr system).The mixtures were then fired at 1200๐C before using as ceramic pigment in a glazed stoneware. 10 wt%of the fired waste and the prepared pigments were separately added into the transparent glaze and were then coated on the biscuit samples before firing at 1200 °C. The results shown that the glazed samples (green, pink, and brown) were successfully produced the ceramic pigment using the tanned leather waste as chromium source. Moreover, the leaching of Lead (Pb), Cadmium (Cb) and Chromium (Cr) from glazed product were detected.